Cognitive foundations of learning from testimony. [article]. - Harris, Paul L.
Humans acquire much of their knowledge from the testimony of other people. An understanding of the way that information can be conveyed via gesture and vocalization is present in infancy. Thus, infants seek information from well-informed interlocutors, supply information to the ignorant, and make sense of communicative acts that they observe from a third-party perspective. This basic understanding is refined in the course of development. As they age, children's reasoning about testimony increasingly reflects an ability not just to detect imperfect or inaccurate claims but also to assess what inferences may or may not be drawn about informants given their particular situation. Children also attend to the broader characteristics of particular informants?their group membership, personality characteristics, and agreement or disagreement with other potential informants. When presented with unexpected or counterintuitive testimony, children are prone to set aside their own prior convictions, but they may sometimes defer to informants for inherently social reasons. -- (from the author)